2014
DOI: 10.1007/s00359-014-0945-8
|View full text |Cite
|
Sign up to set email alerts
|

Moth hearing and sound communication

Abstract: Active echolocation enables bats to orient and hunt the night sky for insects. As a counter-measure against the severe predation pressure many nocturnal insects have evolved ears sensitive to ultrasonic bat calls. In moths bat-detection was the principal purpose of hearing, as evidenced by comparable hearing physiology with best sensitivity in the bat echolocation range, 20-60 kHz, across moths in spite of diverse ear morphology. Some eared moths subsequently developed sound-producing organs to warn/startle/ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 69 publications
0
23
2
Order By: Relevance
“…Collective materials Defense swarming Japanese honeybees [574] Material-like swarm Honeybees [573] Magnetic orientation Termites [631] Tree nesting Weaver ants [653] Water active properties Designed wettability Desert beetle [161] Hydrophobic surface Planthopper, [155] mosquitos, [157] green bottle fly [160] Thin flexible membranes Locomotion Locomotive method Mayflies [654] Wing design Bumblebees, [102][103][104][105] dragonflies [94,106,107,112] Mechanosensation Subgenual organs Ground wetas [248,249] Tympanum Cicadas [235] Sound production Tymbal sound production Tiger moths, [269] cicadas [254,266] Thermoregulation Thermosensing Dark-pigmented butterflies [393,655] Water active properties Hydrophobic surface Mosquitos [178] Water-active behavior Termites [177,656] Chemical/other Chemical sensing and defense…”
Section: Physical Adhesive Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collective materials Defense swarming Japanese honeybees [574] Material-like swarm Honeybees [573] Magnetic orientation Termites [631] Tree nesting Weaver ants [653] Water active properties Designed wettability Desert beetle [161] Hydrophobic surface Planthopper, [155] mosquitos, [157] green bottle fly [160] Thin flexible membranes Locomotion Locomotive method Mayflies [654] Wing design Bumblebees, [102][103][104][105] dragonflies [94,106,107,112] Mechanosensation Subgenual organs Ground wetas [248,249] Tympanum Cicadas [235] Sound production Tymbal sound production Tiger moths, [269] cicadas [254,266] Thermoregulation Thermosensing Dark-pigmented butterflies [393,655] Water active properties Hydrophobic surface Mosquitos [178] Water-active behavior Termites [177,656] Chemical/other Chemical sensing and defense…”
Section: Physical Adhesive Systemsmentioning
confidence: 99%
“…[254,[266][267][268] Tiger-moth tymbals are modified regions of the thorax that produce high-frequency, tuneable clicks in the 40-80 kHz range. [269] Sounds from these clicks, unlike cicada songs, serve a dual purpose and are used both as mating signals and in acoustic aposematism against bats. The moths are advertising to bats that they are toxic and the sounds "jam" the sonar of motheating bats to deter them.…”
Section: Sound Production In Insectsmentioning
confidence: 99%
“…The use of calling songs by moths has been confirmed in only a few species (Conner, 1999;Greenfield, 2014), but it has been increasingly reported that moths communicate acoustically with male courtship songs (Nakano et al, 2015). Male moths produce courtship songs after they have approached close to (within a few centimeters of) a female that has released sex pheromones to attract males from a long distance.…”
Section: Introductionmentioning
confidence: 99%
“…The hearing organ of flies for example, the Johnston's organ, which is located within the antennae (Child, 1894;Eggers, 1924) detects particle velocity leading to a high resolution of the temporal pattern of a sound stimulus (for review see Albert & G€ opfert, 2015). Another mechanism to perceive temporal patterns is achieved by the tympanal membranes of notodontid moths (for review see Nakano, Takanashi, & Surlykke, 2015). The moths' organs often possess only a single receptor cell that is tuned to bat echolocation calls (Surlykke, 1984;Fullard, 1984Fullard, , 1987 with the tuning based on the mechanical resonance of the tympanal membrane.…”
Section: Introductionmentioning
confidence: 99%